PELATIHAN MATERI AKUNTANSI INVESTASI DALAM OBLIGASI BAGI SEKOLAH KRISTEN YUSUF JAKARTA - Emillia Sastra (PROSIDING SERINA, 2021)
This Community Service Activity (PKM) is one of the manifestations of the College Tri Dharma, which is to provide benefits to the community. For this activity, the PKM implementation team conducted accounting training for the partners of SMA Kristen Yusuf, which is located at the Jembatan Dua area. This PKM activity began with a meeting to explore the needs of the Yusuf Christian High School in this collaboration. A good response was received from the Yusuf Christian High School so that the PKM implementation team submitted a proposal for activities to LPPM Tarumanagara University. This training activity is carried out in the form of lectures, discussions, and exercise about accounting for investment activities in bonds. Through this activity, the Yusuf Christian High School students are introduced to the understanding of investments that can be made by individuals and by companies so that the expected financial goals can be realized. The benefits of this PKM activity for the Faculty of Economics and Business, Tarumanagara University are efforts to share experiences and foster good relations with the high school level as a source of students for Tarumanagara University. From the results of the assessment, it shows that SMA Kristen Yusuf students have understood the material well, able to apply investment accounting in bonds and transactions recording that occur in the company. The results of the questionnaire also show that the material provided is useful for them and fosters students' interest in studying accounting at the next level of learning.